SOME FEATURES OF THE DESIGN AND CONSTRUCTION OF UNDERGROUND PUBLIC AND SHOPPING CENTRE WITH PARKING IN MINSK - Pastushkov, V. H.; Pastushkov, H. P. (Science and Transport Progress, 2010)
In the article some features of designing and construction, experimental-and-theoretical researches of structures of the multifunctional underground complex (public shopping center with parking on theIndependencesq. in Minsk) are considered.